Models for BTEX evaluation in cases of oil spill on the sea, using Experimental Desing (Research, Society and Development, 2021)
The objective of this study was to evaluate and obtain mathematical models, using the experimental design methodology, capable of predicting the contamination of benzene, toluene, ethylbenzene and xylenes (BTEX) in cases of oil spillage at sea, and to evaluate the acute toxicity of the soluble petroleum fraction (FSA). The factorial experimental planning was developed to describe the concentration of each compound according to the variables: oil °API, contact time oil/seawater after spillage and ambient temperature. The models presented can be used to quantitatively predict BTEX contamination in seawater with accuracy greater than 99%, within the studied ranges. The contact time oil seawater was the most determining factor in the concentration/contamination of BTEX in the Petroleum FSA. According to CL50% the soluble fraction of oil of °API 39.8 showed higher toxicity, with a LC50% of 46.07 with 1 h, and 11.38 with 96 hours of contact time oil/seawater, while the oil °API 32.8 showed lower toxicity, however presented higher concentrations of BTEX in FSA, this is possibly due to the synergistic effect of other hydrocarbons that became bioavailable to Mysidopsis juniae during the tests. The samples demonstrated potential environmental risk in cases of oil spillage, and these results can help in the development of a risk assessment of oil spills and serve as a useful analytical tool for emergencies.